2021
DOI: 10.1002/cm.21662
|View full text |Cite
|
Sign up to set email alerts
|

Composition and function of ciliary inner‐dynein‐arm subunits studied in Chlamydomonas reinhardtii

Abstract: Motile cilia (also interchangeably called “flagella”) are conserved organelles extending from the surface of many animal cells and play essential functions in eukaryotes, including cell motility and environmental sensing. Large motor complexes, the ciliary dyneins, are present on ciliary outer‐doublet microtubules and drive movement of cilia. Ciliary dyneins are classified into two general types: the outer dynein arms (ODAs) and the inner dynein arms (IDAs). While ODAs are important for generation of force and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 211 publications
(362 reference statements)
1
14
0
Order By: Relevance
“…While ODAs drive ciliary beating, a larger and more diverse set of IDAs tune the waveform (Fig. 1A, right)(Yamamoto et al, 2021). We next examined the IDA(f) subunit Wdr78 and the IDA(a,c,d) subunit Dnali1 and found that each deployed substantially faster than did the ODAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While ODAs drive ciliary beating, a larger and more diverse set of IDAs tune the waveform (Fig. 1A, right)(Yamamoto et al, 2021). We next examined the IDA(f) subunit Wdr78 and the IDA(a,c,d) subunit Dnali1 and found that each deployed substantially faster than did the ODAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Microtubule Inner Proteins (MIPs) project inside the outer doublet microtubules, provide structural stability, and likely regulate axonemal dynein function (Ichikawa and Bui, 2018). The axonemal dyneins, in turn, reside outside these doublet microtubules, and include both the outer and inner dynein arms (ODAs, IDAs) (King, 2018;Yamamoto et al, 2021). In the center of the axoneme are the central pair microtubules and these are surrounded by the central apparatus (Loreng and Smith, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only three but none of the other subunits of IDA were enriched. IC140 and IC97 are components of double-headed dyneins while p28 is a component of dynein a, c, and d [ 1 ]. Taken together, these data suggest that FBB18 participates in the folding/maturation of most of the DHCs and likely some of the IDA accessory components before they are assembled into large dynein complexes for transporting into cilia though we do not exclude other possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to propelling sperm movement, it functions in circulation of cerebrospinal fluid in the brain, mucus clearance in airways, egg movement in fallopian tubes, sperm transport from testis to epididymis and nodal flow in embryonic node. Ciliary beating requires axonemal dyneins, which consist of heavy chains (HCs), intermediate chains (ICs), light intermediate chains (LICs) and light chains (LCs) while the exact composition of each dynein differs [ 1 , 2 ]. The axonemal dyneins are organized into outer and inner dynein arms (ODAs and IDAs) as revealed by electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The internal structure of most motile cilia and flagella consists of nine parallel doublet microtubules arranged around a central pair of singlet microtubules ( Figure 1A ). Force for propulsion is provided by thousands of dynein motors, anchored in two rows along one side of each doublet and organized into multi-headed complexes called the inner and outer dynein arms (DiBella 2001; Yamamoto 2021), that can walk along the microtubule of the adjacent doublet.…”
Section: Introductionmentioning
confidence: 99%